Public awareness and understanding on sustainable development in creating sustainable campus - Dola, Kamariah; Saadatian, Omidreza; Askari, Amir Hossein (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
Universities are the most appropriate place to promote change through innovative ideas, activities and researches. However, in terms of facilitating sustainable development, much need to be done as it has not been the upmost priority. This paper explores the campus community awareness and understanding on sustainable development using questionnaire survey and interviews. Findings revealed that majority of campus community understand and support the need for creating sustainable campus although they have not fully embraced the meaning of sustainable development. Results also indicate facilitating and hindering factors for sustainable development awareness. It is acknowledged that the public awareness and understanding of sustainable development and empowerment will produce the kind of strong foundation to create a successful sustainable campus. This study provides suggestions suggestions on creating better awareness and understanding on sustainable development